Peran Augmented Reality dalam Memperkenalkan Organ Pencernaan Manusia pada Anak Sekolah Dasar - Aditya Pranoto; Muhammad Zakariyah (STMIK Budi Darma, 2023)
The human digestive organ, an important part of converting food into energy needed by the body, involves organs such as the stomach, small intestine, large intestine, and pancreas. Understanding the complexity of this system at the elementary school (SD) level is recognized as an important foundation. However, current learning methods still rely on textbooks and teaching aids, this makes the learning atmosphere less interactive because it is too focused on the teacher. In overcoming these problems, Augmented Reality (AR) technology emerged as an innovative solution. AR presents virtual objects in the physical world, creating a more immersive and interactive learning experience. Augmented Reality (AR) is a technology that combines digital content in real-time and translates it into the real world. The method used in this technology is Marker-based Tracking, an AR development technique that uses 2-dimensional markers with certain patterns that are read by the cellphone camera. Using this technology can help elementary school children understand the structure and functionality of human digestive organs by displaying them virtually, making it easier to understand the human digestive organ. Thus, AR-based introduction to human digestive organs for elementary school children could be an effective solution.